PROMOTING SOCIAL AWARENESS THROUGH TOTAL PHYSICAL RESPONSE (TPR) IN TEACHING ENGLISH AT ELEMENTARY SCHOOL - Melani Wahyu Diana; Anis Yona Tyas Wilupi; Deni Setiawan; Diani Nurhajati (STKIP PGRI Jombang, 2022)
AbstractStudents in Indonesia must be equipped with a number of skills to face global competition in the 21st century. One of these skills is soft skills, one of which is social awareness. Ideally, teaching English for elementary school students should be child-friendly. The purpose of learning English in elementary schools is to train students to be able to communicate verbally using English in the context of simple conversations and to train the social awareness to the students. This study aims to describe the stages in training Social Awareness through Total Physical Response (TPR) to teach English at Elementary School. This study used a qualitative approach, and the subjects of this study were the fourth grade, fifth, and sixth grade students. Data collection techniques was carried out by observing offline learning, interviews, and analyzing learning documents, such as textbooks, learning media and so on. It was found out that the social awareness can be trained by selecting learning activity and suitable materials for young learners. It proves that TPR can be used not only to teach English, but also to train the students’ social awareness.Keyword: Social Awareness, TPR (Total Physical Response), English Learning